2008
DOI: 10.1248/cpb.56.1639
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Oseltamivir in Tamiflu Capsules Using Micellar Electrokinetic Chromatography

Abstract: 1639Oseltamivir (Ro 64-0796 or GS4104) is an ethyl ester prodrug of oseltamivir carboxylate (Ro 64-0802 or GS4071) with the chemical name of ethyl (3R,4R,5S)4-acetylamino 5-amino-3(1-ethylpropoxy)1-cyclohexene-1-carboxylate phosphate (1 : 1). Its chemical structure is shown in Fig. 1. It inhibits neuraminidase activity in influenza A and B viruses. The activity of the enzyme is essential for the spread of infectious virus in the body. Oseltamivir is an effective therapeutic agent against pandemic influenza str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Until present, many publications have been reported describing the use of MEKC technique for pharmaceutical drug separation and determination from various pharmaceutical dosage forms ( e.g. for quality control) 231–239. In an infant formula, melamine was determined by using CE with online preconcentration techniques (FASS and sweeping), and the researcher concluded from the results that this study showed a great potential for the sweeping‐MEKC method as a tool for fast screening of melamine in infant formulas 239.…”
Section: Selected Applicationsmentioning
confidence: 81%
“…Until present, many publications have been reported describing the use of MEKC technique for pharmaceutical drug separation and determination from various pharmaceutical dosage forms ( e.g. for quality control) 231–239. In an infant formula, melamine was determined by using CE with online preconcentration techniques (FASS and sweeping), and the researcher concluded from the results that this study showed a great potential for the sweeping‐MEKC method as a tool for fast screening of melamine in infant formulas 239.…”
Section: Selected Applicationsmentioning
confidence: 81%
“…This sweeping protocol has also been applied under basic conditions (BGE with borate buffer at pH over 8.5–10), but only three approaches have been reported. The first one, concerning the determination of picoxystrobin and pyraclostrobin in urine samples 37, the second one dealing with the analysis of the antiviral drug, oseltamivir, and its hydrolysed product in Tamiflu capsules 38 and the third one devoted to the determination of three neutral steroids (testosterone, progesterone and testosterone propionate) 39. As expected, the enhancement factors were lower than those obtained by the sweeping protocol in acidic medium (EOF suppression): only about a 15‐ to 20‐fold improvement in sensitivity can be achieved.…”
Section: Approaches For Improving Sensitivitymentioning
confidence: 99%
“…These methods include: HPLC/UV detection or fluorescence detection after derivatization with naphthalenedialdehyde/potassium cyanide and HPLC–MS . Micellar electrokinetic chromatography and capillary zone electrophoresis were also applied for the determination of OST in capsules. Only two spectrophotometric methods with low sensitivity were developed for the determination of OST in capsule form .…”
Section: Introductionmentioning
confidence: 99%